The Influence of Student Motivation, Exemplary, Personality and GPAI Learning Strategies on the Growth of Character Values in State Senior High School Students in Salatiga City - Amin Nurbaedi; Sugiyo Sugiyo; Dardiri Hasyim (Journal Research of Social Science, Economics, and Management, 2022)
A teacher is a very important figure, because they will grow to be role models for their students. The position of teachers as second parents for students is very strategic in order to prepare the nation's next generation of quality. This study aims to determine the relationship of a variable with other variables using multiple linear regression test. Regression analysis is used to test the relationship between two or more variables, especially to explore the pattern of relationships whose models are not fully known. The research used is a quantitative approach using a correlational design. The results of this study are: 1) Motivation has a positive and significant effect on the growth of character values ??in State Senior High School students in Salatiga City; 2) Exemplary has a positive and significant effect on the growth of character values ??in state high school students in Salatiga City. 3) Personality has a positive and significant effect on the growth of character values ??in State Senior High School students in Salatiga City; 4) The GPAI learning strategy has a positive and significant effect on the growth of character values ??in state high school students in Salatiga City.